2018
DOI: 10.1101/362574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic correlations between pain phenotypes and depression and neuroticism

Abstract: 19Correlations between pain phenotypes and psychiatric traits such as depression and 20 the personality trait of neuroticism are not fully understood. The purpose of this study 21 was to identify whether eight pain phenotypes, depressive symptoms, major 22 depressive disorders, and neuroticism are correlated for genetic reasons. Eight pain 23 phenotypes were defined by a specific pain-related question in the UK Biobank 24 questionnaire. First we generated genome-wide association summary statistics on 25 each p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 45 publications
5
29
1
1
Order By: Relevance
“…It is likely that the locus tagged by rs7628207 contains regulatory elements that influence transcription of adjacent genes. Interestingly, RNF123 gene expression has been linked to the risk of major depression 30 , and major depressive disorders are genetically correlated with pain 25 . As the AMIGO3 gene transcript (the CNS-related gene bearing the GIP1associated SNP rs7628207 in its intron) was not present among the list of probes analyzed in the GTEx 31 and Westra projects 32 , we could not infer pleiotropy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the locus tagged by rs7628207 contains regulatory elements that influence transcription of adjacent genes. Interestingly, RNF123 gene expression has been linked to the risk of major depression 30 , and major depressive disorders are genetically correlated with pain 25 . As the AMIGO3 gene transcript (the CNS-related gene bearing the GIP1associated SNP rs7628207 in its intron) was not present among the list of probes analyzed in the GTEx 31 and Westra projects 32 , we could not infer pleiotropy.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, even very large genome-wide association studies provide only a limited number of replicated loci and rather low SNP-based heritability. Evidence from recent studies indicates that pain at different anatomical sites shares a common genetic component [24][25][26] . This suggests that combining several pain phenotypes in a single analytical framework may facilitate the discovery of common genetic factorschronic musculoskeletal pain genes and pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, there is also an increasing trend in the current literature regarding the etiology of neuroticism, and also its connections with the risk of affective disorders and pain vulnerability, evidencing the mediator role of personality for pain and affective disorders [ 165 ]. Thus, neuroticism was described as a stable, genetically-based dimension of temperament, which can be viewed as a consequence or response to elevated stress, being related to the psychological profile of every individual and based on a multitude of endo- and exogenous factors fulfilling the role of amplifiers [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genetic correlations were performed for example, by linkage disequilibrium score regression method in a UK cohort that consisted of 151,922–226,683 individuals. By estimating the genetic correlation of 8 pain phenotypes with other psychiatric traits, Meng et al [ 166 ] demonstrated that all pain phenotypes are heritable (h2 = 0.31) and they have a strong and positive correlation with other pervasive low moods by sharing to some extent a similar mechaniscistic pattern.…”
Section: Discussionmentioning
confidence: 99%